2016
DOI: 10.1093/cercor/bhw092
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Stages of Moment-to-Moment Processing in the Cinguloopercular and Frontoparietal Networks

Abstract: Control of goal-directed tasks is putatively carried out via the cinguloopercular (CO) and frontoparietal (FP) systems. However, it remains unclear whether these systems show dissociable moment-to-moment processing during distinct stages of a trial. Here, we characterize dynamics in the CO and FP networks in a meta-analysis of 5 decision-making tasks using fMRI, with a specialized "slow reveal" paradigm which allows us to measure the temporal characteristics of trial responses. We find that activations in left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
72
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 66 publications
7
72
0
Order By: Relevance
“…This may reflect similar computational processes occurring for harm/welfare-based transgressions and conventional transgressions, potentially involving performance reporting/monitoring (c.f. Droutman et al, 2015; Gratton et al, 2016), but that these occur more strongly for harm/welfare-based transgressions. Two caveats should be noted with respect to this conclusion, however.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…This may reflect similar computational processes occurring for harm/welfare-based transgressions and conventional transgressions, potentially involving performance reporting/monitoring (c.f. Droutman et al, 2015; Gratton et al, 2016), but that these occur more strongly for harm/welfare-based transgressions. Two caveats should be noted with respect to this conclusion, however.…”
Section: Discussionmentioning
confidence: 95%
“…An alternative view regarding the function of these regions has suggested that they play a more attentional role and are implicated in initializing a task set and maintaining it within a trial (Dosenbach et al, 2006; Power & Petersen, 2013; Sestieri, Corbetta, Spadone, Romani, & Shulman, 2014). It is argued that they play a role in performance reporting when adjustments are required by the task (Gratton et al, 2016). The current study was not designed to, and cannot distinguish, between these accounts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, the FPN has been involved in self-regulation, allowing people to control their thoughts, emotions, behaviors, and desires (Kelley, Wagner, & Heatherton, 2015). In fact, control of goal-directed tasks has been carried out via the frontoparietal systems Gratton et al, 2016). On the other hand, the inferior frontal-parietal-ventral insula network showed a greater attentional bias effect for cocaine cues, which was interpreted as the involvement of this functional network in orienting stimulus-driven attention and the detection of the salience of behaviorally relevant stimuli (Kilts et al, 2014).…”
Section: Frontoparietal Network With Differences In Sensitivity To Rementioning
confidence: 99%